Relative humidity sensor employing tapered plastic optical fiber coated with seeded Al-doped ZnO - Harith, Z. (Elsevier B.V., 2017)
A relative humidity sensor operating on intensity modulation principle is proposed and demonstrated using a tapered plastic optical fiber (POF) that is coated with seeded Al-doped ZnO nanostructures. The POF was tapered by mechanical etching and then coated with seeded Al-doped ZnO nanostructures using sol-gel immersion method with different mol% of Al nitrate that acted as dopant. It was found that 1 mol% of Al nitrate produced the best performance compared to other doping concentrations. Then the performances of sensors fabricated using seeded and non-seeded coating methods with 1 mol% of Al-doped ZnO were compared and investigated. The sensor developed using seeded coating method showed a better sensitivity of 0.0386 mV/%, as opposed to the other sensor which registered a sensitivity of 0.0148 mV/%. The results show that tapered POF with Al-doped ZnO nanostructures deposited using seeded coating method is excellent for detecting changes in relative humidity.